2022
DOI: 10.7759/cureus.22766
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Operative Digital Templating Aids Restoration of Leg-Length Discrepancy and Femoral Offset in Patients Undergoing Total Hip Arthroplasty for Primary Osteoarthritis

Abstract: BackgroundPre-operative planning and templating is a crucial pre-requisite for total hip arthroplasty (THA). Recently, the use of digital radiography has allowed templating to be digitalised instead of traditional methods involving the use of radiograph transparencies. The primary aim of this study was to compare the accuracy in correction of leg length discrepancy (LLD) and restoring femoral offset in patients undergoing THA for primary osteoarthritis with pre-operative digital templating (PDT) versus convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Preoperative templating has been generally confirmed as fundamental for successful THA, and the mean postoperative LLD is significantly lower in patients who had preoperative templating than in others. 12,25 The template for the femoral stem is always placed on the contralateral side of the femur to select the femoral bony resection level to reduce LLD. Our study reveals the importance of LLD in patients after neck fracture and planning, which is likely the same in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative templating has been generally confirmed as fundamental for successful THA, and the mean postoperative LLD is significantly lower in patients who had preoperative templating than in others. 12,25 The template for the femoral stem is always placed on the contralateral side of the femur to select the femoral bony resection level to reduce LLD. Our study reveals the importance of LLD in patients after neck fracture and planning, which is likely the same in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Leg-length difference (LLD) is often calculated using the vertical distance between the inferior teardrop point and the tip of the lesser trochanter. 11,12 A recent study demonstrated that before surgery roughly 1 in 6 patients have an LLD of >10 mm when measured from either the lesser trochanter or centre of the femoral head (COH). 13 Leg length is the second-leading cause of litigation against US surgeons.…”
Section: Introductionmentioning
confidence: 99%